A "Stressed" Alfalfa-Based Cropping System Leads to the Selection of Quizalofop-Resistant Italian Ryegrass (Lolium perenne ssp. multiflorum). Issue 4 (December 2016) - Collavo, Alberto; Panozzo, Silvia; Allegri, Antonio; Sattin, Maurizio
Abstract : Italian ryegrass populations investigated in this study were harvested in an alfalfa-based cropping system. In that system, the agronomic practices and chemical weed management, based on the use of aryloxyphenoxy-propionates herbicides (i.e., quizalofop ethyl ester), were optimized to obtain a dual seed–forage production. Five of seven populations tested were confirmed resistant to quizalofop ethyl ester with resistance indexes ranging from 4.5 to >209. Both target- and nontarget-site resistance mechanisms were most likely involved. Three allelic variants were detected (Ile-1781–Leu, Trp-2027–Cys, and Ile-2041–Asn) in four resistant populations, whereas no known mutations were found in one resistant population. The herbicide treatment on Italian ryegrass plants at different phenological stages suggested that to control regrowth, it is necessary to use two to fives times the herbicide dose suitable for younger plants. This situation is encountered in fields when Italian ryegrass plants need to be controlled to maximize the alfalfa seed production, and it is comparable to using a sublethal herbicide dose, leading to the selection of herbicide-resistant biotypes. In such a situation, the cropping system is not sustainable, and integrated weed management should be implemented to deplete the soil weed seed bank and prevent new weed seed production.